Publisher Correction: A community-based transcriptomics classification and nomenclature of neocortical cell types - Yuste, Rafael; Hawrylycz, Michael; Aalling, Nadia; Aguilar-Valles, Argel; Arendt, Detlev; Arnedillo, Ruben Armananzas; Ascoli, Giorgio A.; Bielza, Concha; Bokharaie, Vahid; Bergmann, Tobias Borgtoft; Bystron, Irina; Capogna, Marco; et al. (Nature Neuroscience, 2021)
A Correction to this paper has been published: 10.1038/s41593-020-00768-3.